Fluorene‐based copolymers with donor–acceptor units on the side chain and main chain: Synthesis and application in polymer solar cells. Issue 5 (14th June 2013) - Hou, Qiong; Liu, Jungen; Jia, Tao; Luo, Suilian; Shi, Guang
ABSTRACT Two narrow band gap fluorene‐based copolymers with donor–acceptor (D–A) structure on the polymer side chain and/or main chain are synthesized by Pd‐catalyzed Stille coupling reactions. The two copolymers have excellent thermal stability. The effects of D–A structure on the main and side chains on the absorption and electrochemical properties are studied. The copolymer PF‐BTh‐DBT with D–A structure both on the main and side chains has broader and stronger absorption and narrower band gap than the copolymer PF‐BTh with only a pendent D–A structure. The power conversion efficiency of the assembled solar cell using PF‐BTh‐DBT as donor and PC71BM as acceptor is 1.6% with open‐circuit voltage (Voc) 0.84 V under simulated AM 1.5 G solar irradiation (100 mW/cm2). © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 3276–3281, 2013